Treating explosive kids: the collaborative problem-solving approach - Greene, Ross W. (Guilford Press, 2006)
Explosive children and adolescents : the need for a different paradigm -- Identifying pathways and triggers -- Options for handling problems : three plans -- Plan B basics -- Beyond the basics -- Skills trained with Plan B -- Collaborative problem solving in schools -- Collaborative problem solving in therapeutic/restrictive settings -- Last call.